High-Quality Development of the Petrochemical Industry in China - Dai Houliang (《中国工程科学》杂志社, 2021)
The petrochemical industry is a pillar for China’s economy and a key field for supporting the high-quality development of the manufacturing sector. In this article, we examine China’s petrochemical industry using field research, seminar discussion, and document analysis methods. Although China is at the forefront of petrochemical development worldwide, the development quality of the petrochemical industry still needs to be improved, the product supply is insufficient, and technological innovation is lacking. To promote China’s petrochemical industry up to the middle- and upper-end of the global industrial and value chains, the top-level design should be improved to upgrade the industry in terms of quality and efficiency, and a market-oriented capacity control mechanism should be established to shift the driving forces for development. Moreover, China should focus on technological innovation to promote the core competitiveness of the industry; optimize its domestic business environment to facilitate fair competition; improve environmental policies to promote the safe and green transformation of the petrochemical industry; and deepen international cooperation among countries along the Belt and Road.